Spontaneous Progressive Muscle Weakness with Persistent Leukocytosis - Sameer A. Hirji; Manish M. Karamchandani; Jonathan W. Scott; Matthew T. Menard (Case Reports in Surgery)
Iliacus compartment syndrome is a rare clinical condition which can result in a severe, unilateral, femoral neuropraxia. Recognition of this syndrome as the cause of a developing neuropathy is often delayed given a lack of familiarity with this clinical diagnosis and the retroperitoneal location of the iliacus muscle. Prompt diagnosis is important to avoid risk of consequent muscle necrosis, rhabdomyolysis, and possibly permanent nerve injury. We describe a case of iliacus compartment syndrome in an elderly, frail woman with end-stage renal disease, anticoagulated for atrial fibrillation, who presented with subacute, progressive lower extremity muscle weakness and pain in the setting of complicated metabolic derangements. She was found to have a spontaneous large hematoma in her left iliacus muscle on computed tomography scan. Despite an initial diagnostic delay, she was successfully managed with an iliacus fasciotomy, which led to complete resolution of her symptoms.